Sobrepeso/obesidade e doença hepática gordurosa não alcoólica em adolescentes com fenilcetonúria - Adriana Márcia Silveira (2020)
Introduction: Phenylketonuria (PKU) is an inborn error of metabolism, due to loss or decrease in the activity of the enzyme phenylalanine hydroxylase. The diet, with restriction of natural proteins and use of phenylalanine-free amino acid formula plays a key role in its treatment. The peculiarities of the diet have led to the hypothesis of predisposition to overweight/obesity which, on the other hand, is suspected of predisposing to non-alcoholic fatty liver disease (NAFLD). Are adolescents with PKU more predisposed to developing overweight/obesity and NAFLD? Objective: To evaluate overweight/obesity and NAFLD in adolescents with PKU undergoing exclusive dietary treatment. Methods: Cross-sectional study with 101 adolescents with PKU between 10 years and 20 years incomplete between 2017/18. Anthropometric, biochemical assessments, determination of food consumption and abdominal ultrasound were performed, with classification of the hepatorrenal index. The patients were divided into two groups, according to their nutritional status: one with overweight/obese individuals, the other with normal weight/low BMI. A subgroup was formed with adolescents aged 13-17 years for comparison with the prevalence of overweight/obesity in healthy schoolchildren of the same age. Results: The prevalence of overweight/obesity was 27.7% and there was no gender predominance. The multivariate analysis indicated high blood concentrations of phenylalanine, LDL-cholesterol and elevation of the HOMA index as predictive factors and increasing age as a protective factor for overweight/obesity. The comparison of the prevalence of overweight/obesity among 46 patients aged 13-17 years with schoolchildren of the same age did not reject the hypothesis of equality. The assessment of the hepatorrenal index detected the presence of NAFLD in 26 (25.7%) adolescents, without distinction between genders or association with overweight/obesity, suggesting that PKU and/or diet may contribute to NAFLD. The final model of the multivariate analysis showed a sensitivity of 26.1% and specificity of 94.7%, indicating the need to study other variables. The specificity of the final model suggested a lower possibility of NAFLD in those of older age, normal or elevated alkaline phosphatase levels, lower consumption of carbohydrates and lipids and adequate consumption of proteins. Conclusion: The prevalence of overweight/obesity in adolescents with PKU was similar to that found among adolescents without the disease. High concentrations of Phe, and LDL cholesterol and HOMA index above the reference were predictive factors of the same and higher age protective factor. PKU and/or the diet used in its treatment may represent a risk of NAFLD, regardless of gender, and nutritional status. The specificity of the final model suggested the possibility of lower NAFLD in those of older age, normal/high alkaline phosphatase levels, lower consumption of carbohydrates and lipids and adequate consumption of proteins.